THE INFLUENCE OF CUSTOMER RELATIONSHIP MANAGEMENT, CUSTOMER SATISFACTION QUALITY OF SERVICE AND CUSTOMER LOYALTY (Empirical Study On Corporate Travel Organizers Umrah and Hajj PT. Travel Albadriyah) - Subaebasni, Subaebasni; Risnawati, Henny; Anoesyirwan Moeins (Dinasti International Journal of Management Science, 2019)
Every company should be able to understand the behavior of consumers in the target market because the survival of the company as an organization that seeks to meet the needs and desires of consumers rely heavily on the behavior of consumers. Through an understanding of consumer behavior, the management company can develop appropriate strategies and programs to take advantage of existing opportunities and outperform their competitors. Therefore, the quality of good service and build relationships with customers able to accomplish the goals of the company. It certainly needs to be an active part of all employees and those involved in the provision of services. (MORA, 2017). Based on the analysis and discussion that has been described on the effect of customer relationship management, service quality, and customer satisfaction to customer loyalty in Corporate Travel Organizers Umrah and Hajj PT. Travel Albadriyah, it can be concluded that customer relationship management, service quality, and customer satisfaction proved to influence jointly on customer loyalty Corporate Travel Organizers Umrah and Hajj PT. Travel Albadriyah. As this study is descriptive and verification, using the survey method.